Prospective teachers' mathematical knowledge: Relating representations as design principle for developing knowledge of non-local mathematics for teaching in abstract algebra - Dellori, Anna; Wessel, Lena (Proceedings of the Thirteenth Congress of the European Society for Research in Mathematics Education (CERME13))

Entwicklung und Erprobung von professionsorientierten Lernumgebungen zur Wissensvernetzung in der Algebra - Dellori, Anna; Wessel, Lena (Beiträge zum Mathematikunterricht 2022. 56. Jahrestagung der Gesellschaft für Didaktik der Mathematik)

Brushing-up DLs to Cope with Imperfect Data (Abstract of Joint DL+NMR Invited Talk) - Turhan, Anni-Yasmin (Proceedings of the 36th International Workshop on Description Logics {(DL} 2023) co-located with the 20th International Conference on Principles of Knowledge Representation and Reasoning and the 21st International Workshop on Non-Monotonic Reasoning {(KR} 2023 and NMR 2023)., Rhodes, Greece, September 2-4, 2023)

Identification and prediction of standard times in machining for precision steel tubes through the usage of data analytics - Weller, Julian; Roesmann, Daniel; Eggert, Sönke; von Enzberg, Sebastian; Gräßler, Iris; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

First steps towards real-time assessment of attentional weights and capacity according to TVA - Banh, Ngoc Chi; Scharlau, Ingrid (Abstracts of the 65th TeaP)

Entwurfsmuster: Fachsensible wissenschaftliche Begleitung - Sloane, Hannah Sabrina; Heidebrecht, Jana

„Jede*r von uns sieht die Situation eben unterschiedlich – das ist zwar eine Schwierigkeit, aber auch eine Bereicherung“ - Schuldt, Alessa; Palm, Manfred; Neumann, Phillip; Böhm-Kasper, Oliver; Demmer, Christine; Lütje-Klose, Birgit (Zeitschrift für Konzepte Und Arbeitsmaterialien für Lehrer*innenbildung Und Unterricht)
Die Rollenspiel-Methode ist ein handlungs- und anwendungsbezogenes Instrument, um Studierende bereits während der universitären Ausbildung für unterschiedliche professionelle Sicht- und Handlungsweisen zu sensibilisieren. In diesem Sinne stellt der folgende Beitrag ein Rollenspiel vor, welches als hochschuldidaktisches Material für die inklusionssensible Lehrer*innenbildung genutzt werden kann und Studierende auf zukünftige multiprofessionelle Kooperationshandlungen in der schulischen Praxis vorbereiten soll. Dieses bietet einen geeigneten Anlass, um die professionsübergreifende Zusammenarbeit „gefahrlos“ im Rahmen einer fiktiven kollegialen Fallkonferenz zu erproben sowie unterschiedliche pädagogische Professionsverständnisse aufzudecken und zu reflektieren. Darüber hinaus werden erste Durchführungserfahrungen und Evaluationsergebnisse diskutiert, die im Zuge der wissenschaftlichen Begleitforschung der Teilmaßnahme „Multiprofessionelle Kooperation in inklusiven Ganztagsschulen“ des Bielefelder QLB-Projekts BiProfessional erhoben wurden.
Keywords: Rollenspiel; mulitprofessionelle Kooperation; inklusionssensible Lehrerbildung; Hochschuldidaktik; Blended Learning

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
In spray-flame synthesis of nanoparticles, a precise understanding of the reaction processes is necessary to find optimal process parameters for the formation of the desired products. Coupling the chemistries of flame, solvent, and gas-phase species initially formed from the particle precursor in combination with the complex flow geometry of the spray flame means a special challenge for the modeling of the reaction processes. A new burner has been developed that is capable to observe the reaction of precursor solutions frequently used in spray-flame synthesis. The burner provides an almost flat, laminar, and steady flame with homogeneous addition of a fine aerosol and thus enables detailed investigation and modeling of the coupled reactions inde-pendent of spray formation and turbulent mixing. With its two separate supply channel matrices, the burner also enables the use of reactants that would otherwise react with each other already before reaching the flame. These features enable the investigation of a wide range of flame-based synthesis methods for nanoparticles and, due to the flat-flame geometry, kinetics models for these processes can be developed and validated. This work describes the matrix burner development and its gas flow optimization by simulation. Droplet-size dis-tributions generated by ultrasonic nebulization and their interaction with the burner structure are investigated by phase-Doppler anemometry. As an example for nanoparticle-for ming flames from solutions, iron-oxide nanoparticle-generating flames using iron(III) nitrate nonahydrate dissolved in 1-butanol were investigated. This effort includes measurements of two-dimensional maps of the flame temperature by a thermocouple and height-dependent concentration profiles of the main species by time-of-flight mass spectrometry. Exper-imental data are compared with 1D simulations using a reduced reaction mechanism. The results show that the new burner is well suited for the development of reaction models for precursors supplied in the liquid phase usually applied in spray-flame synthesis configurations.& COPY; 2022 The Combustion Institute. Published by Elsevier Inc. All rights reserved.
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Polycyclic aromatic hydrocarbons (PAHs) are formed in fuel-rich and sooting hydrocarbon flames. These compounds and smaller aromatic flame constituents, such as benzene, toluene and naphthalene can be detected by flame-sampling molecular beam mass spectrometry (MBMS). They are readily ionized by photoionization with UV light, either in resonant or non-resonant ionization processes. The multiphoton ionization of benzene, toluene, and styrene with MBMS detection was investigated as a function of laser power and wavelength and the quantitative relation between ion signal and mole fractions in the flames was established. These measurements were prerequisites for the measurement of quantitative mole fraction profiles of these species in flames of various fuels. In addition, the measurements provide relative mole fraction profiles of various other aromatic flame species. The results are compared to measurements of aromatics in butadiene, propyne, and allene flames by single-photon ionization with vacuum ultraviolet radiation from a synchrotron source and other literature data. (c) 2023 Published by Elsevier Inc. on behalf of The Combustion Institute.

A new dual matrix burner for one-dimensional investigation of aerosol flames - Apazeller, Sascha; Gonchikzhapov, Munko; Nanjaiah, Monika; Kasper, Tina; Wlokas, Irenäus; Wiggers, Hartmut; Schulz, Christof (Proceedings of the Combustion Institute)
Keywords: Physical and Theoretical Chemistry; Mechanical Engineering; General Chemical Engineering

Resonance enhanced multiphoton ionization detection of aromatics formation in fuel-rich flames - Kasper, Tina; Hansen, Nils (Combustion and Flame)
Keywords: General Physics and Astronomy; Energy Engineering and Power Technology; Fuel Technology; General Chemical Engineering; General Chemistry

Human Factors in der integrierten Produktentwicklung - Gräßler, Iris; Roesmann, Daniel; Pottebaum, Jens (Zeitschrift für wirtschaftlichen Fabrikbetrieb)
In der zukünftigen Produktion werden der Aufbau und die Entwicklung der Fähigkeiten der Mitarbeiter:innen ein entscheidender Wettbewerbsvorteil von Unternehmen. In menschenzentrierten Montagesystemen passen sich die Mitarbeiter:innen auf der Grundlage von Lernprozessen an neue und sich ändernde Aufgaben an. Dazu muss der Bezug zu den Fähigkeiten der Mitarbeiter:innen im Zuge der integrierten Produkt-und Prozessentwicklung vorgesehen werden. Daher wurde eine Methodik entwickelt, die diese Fähigkeiten explizit abbildet und sie sowohl in der Entwicklung als auch in der kurzfristigen Personaleinsatzplanung bei der Aufgabenzuordnung berücksichtigt. Zur Anwendung wurde die Methodik prototypisch in einem Software-Werkzeug umgesetzt und in Kombination mit einer diskreten ereignisorientierten Simulation erprobt.
Keywords: Management Science and Operations Research; Strategy and Management; General Engineering

Emerging disciplinary voices - Stock, Ingrid; Karsten, Andrea; Eik-Nes, Nancy Lea (Sakprosa)
While referencing is an important feature of academic writing, many students struggle with using sources. This struggle seems to be due, in part, to the tension students experience when advised to cite sources (i.e., others’ voices) on the one hand, and to demonstrate their own disciplinary voice on the other hand. The aim of this article is to contribute to the understanding of source use, presenting a figure that illustrates gradients of students’ engagement with sources in various sections of their bachelor’s theses. Based on Bakhtin’s idea that a writer’s voice gradually emerges out of others’ words, and the terms knowledge telling and knowledge transforming, we developed a continuum that might help to understand the complexity of source use. We arrived at this continuum through the qualitative exploration of students’ use of sources in 15 bachelor’s theses from the humanities in one Norwegian university. In this article, we illustrate the continuum through extracts from the students’ theses, showing how issues of voice are intertwined with students’ engagement with sources. We propose that understanding the various functions of sources as they are typically used in the disciplines will help students to develop and demonstrate their disciplinary voices. Moreover, the continuum provides a foundation for fruitful discussions of writing practices that raise critical awareness about implicit expectations concerning source use and issues of voice in academic writing.
Keywords: Automotive Engineering

Christine Schwanecke: A Narratology of Drama: Dramatic Storytelling in Theory, History, and Culture from the Renaissance to the Twenty-First Century - Tönnies, Merle

"ProGRess" - Erste Evaluationsergebnisse eines Anti-Prokrastinationstrainings auf Basis des Zürcher Ressourcen Modells (ZRM). - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Reduce procrastination to improve students' health - First analyses of an intervention study. - Schneider, Tamara; Klingsieck, Katrin B.

Vorausschau und Technologieplanung. 17. Symposium für Vorausschau und Technologieplanung - Dumitrescu, Roman; Hölzle, K.

Assessing the Impact of the Powder Production Method on Ceramic-filled Polyamide Composites made by Laser Sintering - Kletetzka, Ivo; Neitzel, Fabian; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
Polymer composites represent the industry standard in injection molding for the production of plastic components with increased requirements in terms of heat resistance and stiffness. In the field of laser sintering (LS), these materials are less common so far. In order to extend the available material variety for the LS process, new ceramic-filled Polyamide 613 powders are investigated within the scope of this work. Here, the resulting properties from two different powder production methods are compared. One filled powder is produced by dry blending and the other powder with the same filler and filling ratio is produced by encapsulating the filler particles inside the polymer particles within the dissolution-precipitation process. It was found that encapsulating the filler particles can provide certain benefits for the processability, for example an improved powder flowability or better filler dispersion. However, encapsulating the filler also alters the thermal properties of the precipitated powder.
Keywords: Additive Manufacturing; Laser Sintering; Filled Materials; Composites; Polyamide 613

Halogen-Free Flame Retardant Powder Materials for Laser Sintering: Evaluation and Process Stability Analysis - Neitzel, Fabian; Kletetzka, Ivo; Schmid, Hans-Joachim (Proceedings of the 34th Annual International Solid Freeform Fabrication Symposium)
The high flammability of components manufactured by laser sintering (LS) using standard polyamide 12 (PA12) powder still severely restricts their use in industries such as electronics, aviation, and transportation. A key factor for the further establishment of LS is the expansion of the material portfolio with, for example, refreshable and halogen-free flame-retardant (FR) powder materials. Accordingly, various halogen-free FRs are investigated in this work and evaluated with respect to their use in LS. First, their decomposition behavior and mode of action are examined. Subsequently, the additives are dry blended with PA12 to investigate properties relevant for LS, such as particle morphology, thermal behavior and melt viscosity. Afterwards, test specimens for UL94 vertical flame-retardancy tests are produced by processing the dry blends on an EOS P3 LS system. Finally, the process stability of the process-aged powder blends is investigated by again examining the thermal behavior and melt viscosity.
Keywords: Additive Manufacturing; Laser Sintering; Flame Retardant; Polyamide 12

Rezension zu D. Pokitsch: Wer spricht? Sprachbezogene Subjektivierungsprozesse in der Schule der Migrationsgesellschaft - Büttner, Denise (Zeitschrift für Deutsch im Kontext von Mehrsprachigkeit (ZDKM))